Pulmonary manifestations of pediatric diseases
Pulmonary Manifestations of Pediatric Diseases is the first comprehensive, practical book strictly focused on diagnosing and treating the full spectrum of respiratory complications of non-pulmonary diseases. Pediatric pulmonologists and other expert specialists present their up-to-date and balanced perspectives on new approaches to therapy and recent advances on everything from HIV/AIDS and transplantation to postoperative complications. The contributors are some of the most distinguished and recognizable physicians in their fields giving you the benefit of accumulated insight and experience. You’ll have everything you need to perform a complete pulmonary consultation in one handy reference